Is There a Relationship Between Body Mass Index and Fluoroscopy Time During Sacroiliac Joint Injection? A Multicenter Cohort Study. Issue 7 (24th December 2015) - McCormick, Zachary L.; Cushman, Daniel; Lee, David T.; Scholten, Paul; Chu, Samuel K.; Babu, Ashwin N.; Caldwell, Mary; Ziegler, Craig; Ashraf, Humaira; Sundar, Bindu; Clark, Ryan; Gross, Claire; et al.
Abstract: Objective. To determine the relationship between BMI and fluoroscopy time during intra-articular sacroiliac joint (SIJ) injections performed for a pain indication. Design. Multicenter retrospective cohort study. Setting . Three academic, outpatient pain treatment centers. Subjects . Patients who underwent fluoroscopy guided SIJ injection with encounter data regarding fluoroscopy time during the procedure and body mass index (BMI). Main Outcome Measure. Median and 25–75% Interquartile Range (IQR) fluoroscopy time. Results . 459 SIJ injections (350 patients) were included in this study. Patients had a median age of 57 (IQR 44, 70) years, and 72% were female. The median BMI in the normal weight, overweight, and obese groups were 23 (IQR 21, 24), 27 (IQR 26, 29), and 35 (IQR 32, 40), respectively. There was no significant difference in the median fluoroscopy time recorded between these BMI classes (p = 0.45). First-time SIJ injection (p = 0.53), bilateral injection (p = 0.30), trainee involvement (p = 0.47), and new trainee involvement (trainee participation during the first 2 months of the academic year) (p = 0.85) were not associated with increased fluoroscopy time for any of the three BMI categories. Conclusions. Fluoroscopy time during sacroiliac joint injection is not increased in patients who are overweight or obese, regardless of whether a first-time sacroiliac joint injection was performed, bilateral injections were performed, a trainee was involved, or a new trainee was involved.